Factors in the Formation of Trust Relationships in the Network of Stakeholders - Bazaliieva Liudmyla V. (Bìznes Inform, 2020)
The article is aimed at defining and systematizing the factors in the formation of trust relationships in the network of stakeholders, which will allow to identify effective and efficient ways and instruments to develop trust. The work substantiates the presentation of the key characteristics of the network of stakeholders – the center of the network, its density and structure – in the form of factors in the formation of trust of the first order. In order to improve the efficiency of programs for the formation of trust in the network of stakeholders, the factors in the formation of trust of the first order are specified. Thus, it is proposed to allocate factors of the second order, such as the level of interest of network participants in the relationship, the form of interest of the network participants, the distribution of the forces of stakeholders in the network according to the Model of Mitchell, the ability of the company to appeal to the network participants, the intensity of interactions between the network participants. An approach to determining the level of interest of network members in relationships is proposed, based on an assessment of counter-flows of interest between the network center company and each stakeholder. The proposed approach enables the network centre company to better distribute its efforts and resources directed towards establishing trust relationships. The dominant form of stakeholder interest is allocated, such as engagement in ensuring the long-term and successful operation of the center company or implementing a project to solve the problem of the center of the network. The ratio of two forms of interest to stakeholders – concern and interest – allows to consider it as a complex phenomenon.